(untitled) (Cadernos de Sociomuseologia, 2009)
Each time more, museology professionals are confronted with terms such as community, social inequality, social inclusion and development in their quotidian. Be it in conferences, publications or museum programmes, these are increasingly recurrent terms which, in great part, translate the dynamics of a relationship between museology and community development that has been constructed since the late 60’s. Although it is not new, such relationship has gone through a major bloom in the early 90’s and arrives today as an emerging priority within the world of museology. A first glance on the subject reveals that very different approaches and forms of action share the efforts in endowing museology with a role in community development today. In addition, despite of its growing popularity, it seems to be some misunderstandings on what the work with community development requires and truly signifies, as can be pointed out in a number of assertions originated from the field of museology. Accompanying such a plural environment, discussions and disagreements about to what extend museology is able to claim a role in social change also mark its affairs with community development. People are faced, indeed, with a rather polemic and intricate scenario. To a great extend, language barriers hinder the exchange of information on current initiatives and previous experiences, as well as on the development of concepts, approaches and proposals. Lack of better interactions among the groups of museology professionals and social actors who carry out different works with community development also contributes to making the potential of museology as a resource for development more difficult to be visualised.